Rice Husk Silica Ceramic Water Filter System - Mustpha @ Mustapha, Siti Sarah Sofia; Ahmad, Sufizar; Jemima Fae James,; Nurul Ain Shuhada Othman, (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Rice-husk Silica, an accommodating, sustainable substance with many uses, is concealed in rice grain husks. It's about recycling waste and turning a readily available resource into a beneficial asset that can be used in many areas. The hard outer layer of rice husks contains silicon dioxide (SiO2), called silica. About 20% of the husk's weight is this layer, which can be used to extract silica. Silica can be removed and processed chemically or thermally to make a high-quality, flexible product. Rice husk silica, once considered a rice cultivation waste, is now being recycled into a fascinating substance with several ecological uses. Its use in filtering systems is promising. Rice husk silica filters are a novel and effective filtration option. It is filter well and can treat industrial effluent and domestic water due to their huge surface area and porous nature. Since rice husks are abundant, they are lightweight, inexpensive, and scalable. Rice husk silica, which can be easily and sustainably sintered at 1200°C, would be used to build a water filtration system in this research. SolidWork simulates the water filter system's careful design and construction. A prototype water filter system would test filters made from prior research. Based on water filter system flow, this study evaluates and records the time taken of water flow.